Factors associated with influenza and pneumococcal vaccine uptake among rheumatoid arthritis patients in Denmark invited to participate in a pneumococcal vaccine trial (Immunovax_RA). (2nd November 2017) - Nguyen, MTT; Lindegaard, H; Hendricks, O; Friis-Møller, N
Abstract : Objective : This study investigates predictors of influenza and pneumococcal vaccine coverage among rheumatoid arthritis (RA) patients, and explores possible differences according to type of RA therapy. Method : RA patients from two clinics in the region of Southern Denmark were informed about the survey during scheduled follow-up visits. The questionnaire included questions concerning previous influenza and pneumococcal vaccine uptake, attitudes about vaccination, and socio-demographic factors. Factors associated with recalled vaccine uptake were assessed by multivariate logistic regression. Results : A total of 192 RA patients completed the survey, 134 (70%) of whom were women and 90 (47%) were aged ≥ 65 years. Sixty-seven patients (35%) received conventional disease-modifying anti-rheumatic drugs (cDMARDs) and 125 (65%) combination therapy with biological disease-modifying anti-rheumatic drugs (bDMARDs). Self-reported uptake of vaccination against seasonal influenza ever was 59% overall; 57% among patients receiving cDMARDs and 61% in patients receiving bDMARDs. Self-reported vaccine uptake against pneumococcal diseases was only 6% overall. Older age, educational level, and information and recommendation by a specialist or general physician were positively associated with influenza vaccine uptake, while there was no significant difference in vaccine uptake according to RA treatment type. Reasons for not being vaccinated included fear of adverse effects, lack of information and recommendation, and perception of good health. Conclusion : We observed a low prevalence of influenza and in particular of pneumococcal vaccinations among RA patients receiving immunosuppressive drugs, with no difference in coverage according to type of RA therapy. More population-specific evidence to support recommendations is required to increase awareness among patients and physicians.